Arahan Mitigasi Bencana Banjir Pada Kecamatan Balikpapan Timur - Sapoetra, Ryo; Mustofa, Umar; Pratomo, Rahmat Aris; Hidayat, Arief (COMPACT: Spatial Development Journal, 2024)
Based on the Balikpapan City Regional Long Term Development Plan (RPJMD) 2021-2026, East Balikpapan District is one of the areas in Balikpapan City that is prone to flood disasters, this is due to the area being intersected by the Makassar Strait and crossed by the Manggar watershed and the large amount of land clearing. illegal activities that are not by government plans. The primary survey in the form of interviews and observation activities was carried out to collect vulnerability and capacity data with stakeholders related to the research such as the Balikpapan City BPBD, community disaster agencies, and sub-district authorities and the secondary survey in the form of a literature study was aimed at collecting vulnerability data. This research seeks to formulate flood disaster mitigation directions using overlay weight analysis to determine the level of disaster risk and triangulation analysis in formulating flood disaster mitigation directions using disaster risk results, policies, and best practices. The results of this research are in the form of structural mitigation, building disaster-resilient infrastructure, and providing logistics and disaster evacuation tools for non-structural mitigation directions, there is an organizational structure for disaster management, provision of evacuation routes, operational standards for disaster management, early warning systems, provision of disaster education, provision of simulations. disaster events, and communication between disaster agencies